The Bonn Handbook of Globality
XXIII, 749 p. 2 illus. in color.
Keywords: This two-volume handbook provides readers with a comprehensive interpretation of globality through the multifaceted prism of the humanities and social sciences. Key concepts and symbolizations rooted in and shaped by European academic traditions are discussed and reinterpreted under the conditions of the global turn. Highlighting consistent anthropological features and socio-cultural realities, the handbook gathers coherently structured articles written by 110 professors in the humanities and social sciences at Bonn University, Germany, who initiate a global dialogue on meaningful and sustainable notions of human life in the age of globality. Volume 1 introduces readers to various interpretations of globality, and discusses notions of human development, communication and aesthetics. Volume 2 covers notions of technical meaning, of political and moral order, and reflections on the shaping of globality.